Os êxitos da história social do trabalho - Aldrin Castellucci; Caio Castro Gerbelli; David P. Lacerda; Melina K. Perussatto; Micaele Irene Scheer; Nauber Gavski da Silva (Revista Mundos do Trabalho)
Editorial da Mundos do Trabalho, volume 12 (2020).